The impact of endocrine-disrupting chemical exposure in the mammalian hypothalamic-pituitary axis - Graceli, Jones B.; Dettogni, Raquel S.; Merlo, Eduardo; Niño, Oscar; da Costa, Charles S.; Zanol, Jordana F.; Ríos Morris, Eduardo A.; Miranda-Alves, Leandro; Denicol, Anna C. (Molecular and cellular endocrinology, 2020)
The hypothalamic-pituitary axis (HP axis) plays a critical and integrative role in the endocrine system control to maintain homeostasis. The HP axis is responsible for the hormonal events necessary to regulate the thyroid, adrenal glands, gonads, somatic growth, among other functions. Endocrine-disrupting chemicals (EDCs) are a worldwide public health concern. There is growing evidence that exposure to EDCs such as bisphenol A (BPA), some phthalates, polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs) and biphenyls (PBBs), dichlorodiphenyltrichloroethane (DDT), tributyltin (TBT), and atrazine (ATR), is associated with HP axis abnormalities. EDCs act on hormone receptors and their downstream signaling pathways and can interfere with hormone synthesis, metabolism, and actions. Because the HP axis function is particularly sensitive to endogenous hormonal changes, disruptions by EDCs can alter HP axis proper function, leading to important endocrine irregularities. Here, we review the evidence that EDCs could directly affect the mammalian HP axis function.